Mesoappendix cyst: a new interesting sequelae of appendicitis - Gunasekaran, Gopalakrishnan; Naik, Debasis; Kandhasamy, Sakthivel Chinnakkulam; Sundarraj, Shankar (International Surgery Journal, 2016)
Appendicitis is the most common cause of an emergency surgery. Initially, appendectomy was the preferred treatment for appendicitis, but nowadays there is a growing trend toward conservative management for acute appendicitis. The common complication of appendicitis includes perforation peritonitis, abscess formation, portal vein thrombosis, and superior mesenteric vein thrombosis while formation of mucinous cysts in mesoappendix as sequelae to appendicitis has not been reported in the literature. We, here, present a case of mesoappendix cyst as sequelae of appendicitis in a 26-year-old male.